Literary afterlife : the posthumous continuations of 325 authors' fictional characters - Drew, Bernard A. (Bernard Alger), 1950- (McFarland & Co., Publishers, 2010)
"This reference book describes literary pastiches in which fictional characters have reappeared in new works after the deaths of the authors. It includes series that have continued under a deceased writer's real or pen name, undisguised offshoots issued under the new writer's name and posthumous collaborations in which a deceased author's unfinished manuscript is completed by another writer"--Provided by publisher.